2021
DOI: 10.3389/fmicb.2021.610389
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Biokinetics: Towards Optimization for Industrial Applications

Abstract: Denitrification is a microbial process that converts nitrate (NO3–) to N2 and can play an important role in industrial applications such as souring control and microbially enhanced oil recovery (MEOR). The effectiveness of using NO3– in souring control depends on the partial reduction of NO3– to nitrite (NO2–) and/or N2O while in MEOR complete reduction of NO3– to N2 is desired. Thauera has been reported as a dominant taxon in such applications, but the impact of NO3– and NO2– concentrations, and pH on the kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…It should be noted that the behaviour of the chemostat and the estimated kinetic parameters are specific to the consortium (dominated by Dechloromonas and Ralstonia ) and are not generalizable to other types of selenate‐reducing bacteria. The μ max estimated for the selenate‐reducing consortium in this study is on the same order of magnitude as values reported for denitrifying bacteria 49 and slightly greater than values reported for other anaerobic microorganisms, such as sulfate‐reducing bacteria 50,51 …”
Section: Resultssupporting
confidence: 66%
“…It should be noted that the behaviour of the chemostat and the estimated kinetic parameters are specific to the consortium (dominated by Dechloromonas and Ralstonia ) and are not generalizable to other types of selenate‐reducing bacteria. The μ max estimated for the selenate‐reducing consortium in this study is on the same order of magnitude as values reported for denitrifying bacteria 49 and slightly greater than values reported for other anaerobic microorganisms, such as sulfate‐reducing bacteria 50,51 …”
Section: Resultssupporting
confidence: 66%
“…Azurin has been a protein of interest for many groups since it exhibits the most blue-shifted Trp emission spectrum of any known protein (∼308 nm) [ [46] , [47] , [48] ] arising from a single Trp residue buried in the interior of the β-barrel domain. It is also interesting as a redox protein that could be used in biotechnology applications focused on its denitrification function and potential uses in nitrate decontamination of water or soil [ [49] , [50] , [51] , [52] ].…”
Section: Introductionmentioning
confidence: 99%
“…Both nitrite and nitrate are forms of nitrogen that plants can readily absorb [66,67]. The last step of the Nitrogen cycle includes the conversion of nitrate into molecular Nitrogen and the activity is carried out by microorganisms [68]. Among different communities of plants, the measurements of denitrification differ [69] (Fig.…”
mentioning
confidence: 99%